Incidence and risk factors for recurrent sexually transmitted infections among MSM on HIV pre-exposure prophylaxis. (1st July 2022) - Zeggagh, Jérémy; Bauer, Rebecca; Delaugerre, Constance; Carette, Diane; Fressard, Lisa; Charreau, Isabelle; Chidiac, Christian; Pialoux, Gilles; Tremblay, Cécile; Cua, Eric; Robineau, Olivier; Raffi, François; et al.
Abstract : Objective: High rates of sexually transmitted infections (STIs) have been reported among pre-exposure prophylaxis (PrEP) users. We wished to assess the incidence and risk factors for recurrent STIs. Design: The ANRS IPERGAY trial was a prospective study investigating PrEP among MSM and transgender women in outpatient clinics in France and Canada. In all, 429 participants were enrolled, offered up to 4 years of PrEP and screened for bacterial STIs (syphilis, chlamydia and gonorrhea) at baseline and every 6 months. Methods: STIs incidence was calculated yearly. Cox proportional hazards model regression was used to explore associations between participants characteristics at baseline and recurrent STI during follow-up. Results: Over a median follow-up of 23 months, bacterial STI incidence was 75, 33, 13, 32 and 30 per 100 person-years for all STIs, rectal STIs, syphilis, gonorrhea and chlamydia, respectively. STI incidence significantly increased from the first year to the fourth year of the study (55 vs. 90 per 100 person-years, P < 0.001). During the study period, 167 participants (39%) presented with more than one bacterial STIs which accounted for 86% of all STIs. Baseline risk factors associated with recurrent STIs in a multivariate analysis were an STI at baseline [hazards ratio: 1.48 (95% confidence interval (CI): 1.06–2.07), P = 0.02], more than eight sexual partners in prior 2 months [hazards ratio: 1.72 (95% CI: 1.21–2.43), P = 0.002] and the use of gamma-hydroxybutyrate [hazards ratio: 1.66 (95% CI: 1.16–2.38), P = 0.005]. Conclusion: STI incidence was high and increased over time. Most STIs were concentrated in a high-risk group that should be targeted for future interventions.